Data breaching in cloud computing caused by man-in-the-middle (MITM) attack / Siti Naquiah Ahmad Tarmizi Lim - Ahmad Tarmizi Lim, Siti Naquiah (2016)
Data breach is one of the biggest issues faced by organization whether in public or private sector. It is an incident where sensitive, protected or confidential data has been viewed, stolen or used by an unauthorized individual. Verizon Data Breach 2014 reported that 73% data breach causes by unauthorized access and stole password. Man-in-the-Middle (MITM) attack is one of the attacks that can gain unauthorized access without the user knows. It is one type of eavesdropping attack that occurs when attacker place himself between users or systems in a communication session. The main objective of this project is to conduct MITM attack, gain unauthorized access and causing data breach. This project also indicates to analyze the security of the https website. Graphical Network Simulator 3 (GNS3) and virtual box have been used to conduct this test in cloud computing environment that is connected to the real network. Using this set-up, attacker machine launched MITM attacks such as DNS Spoofing, session hijacking, SSL hijacking, database hijacking and remote hijacking against victim machines. Result gain shows that attacker able to cause data breach by gaining unauthorized access using stolen password.